Computer Science Curricula 2013 Released. - Sahami, Mehran; Roach, Steve (Communications of the ACM, 2014)
The article reports on the publication of the "Computer Science Curricula 2013" (CS2013) in the fall of 2013. Topics discussed include the objective of CS2013 to balance the growth in the field with the requirement to maintain proposals realistic and implementable in the context of undergraduate education, the series of fundamental software development concepts of Programming Fundamentals, and the topics with less required coverage in CS2013 relative to past guidelines. Important characteristics of CS graduates beyond technical expertise in relation to professional practice are also outlined in CS2013.